Pengembangan Flipbook sebagai Media Pembelajaran Rias Prostetik Luka Berbahan Lateks dan Tepung Terigu bagi Mahasiswa Tata Rias - Vandita Rai Savira; Kokom Komariah (Dinasti Research, 2026)
The objectives of this development are; (1) to know how to develop flipbook media in providing new insights to students; (2) to know the design of prosthetic makeup flipbooks in Indonesian; (3) to know the development of wheat flour and latex as a mixture of ingredients in making prosthetics; (4) to know the feasibility of making prosthetic flipbooks using latex and wheat flour. The method used in this research is Research and Development using the 4D development model, namely; (1) define, is a defining stage which includes problem analysis, needs analysis, literature study and determination of reference products; (2) design, make product designs (drafts) and makeup designs on flipbooks; (3) develop, is product manufacturing, expert validation tests and limited scale product tests; (4) disseminate, includes product dissemination to 30 student panelists. The research was conducted at Rock Regency Housing and Yogyakarta State University. The analysis method used was quantitative and qualitative descriptive analysis. The results of the development show that; (1) flipbook development is made through the collection and preparation of material tools, drafting production, which then produces a prototype flipbook, followed by product validation and is declared feasible (2) the results of validation through material experts and media experts state that it is feasible with the percentage results of 69% and 83%, it can be concluded that the product is declared feasible (3) mixing latex and wheat flour can be used as a reference in making prosthetics. The suggestion given is that there are more and more discussions about prosthetic makeup using flipbook media because of the development of an increasingly advanced era. Continue using AI Cursor?Keep it onTurn Off